2019
DOI: 10.1007/s40744-019-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Nurse and Patient Perceptions and Preferences for Subcutaneous Autoinjectors for Inflammatory Joint or Bowel Disease: Findings from a European Survey

Abstract: Introduction Imraldi™ is a biosimilar of the anti-tumor necrosis factor (TNF) monoclonal antibody adalimumab and was recently approved in Europe for the treatment of various inflammatory conditions. Imraldi is administered via an autoinjector device that features distinct design attributes compared with other biologic TNF inhibitor autoinjectors, such as the Humira (adalimumab) Pen® and Enbrel® (etanercept) MyClic® Pen were developed by the relevant pharmaceutical companies. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…To our knowledge, no comparable study has been conducted on a nationwide basis. A survey conducted among a selected group of patients and nurses in Germany and the United Kingdom focused on the patients' preference for using Imraldi R pen versus Humira R or Enbrel R (etanercept) pens (5). Fenwick and colleagues demonstrated that most of their patients (78%) preferred to use the Imraldi R pen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no comparable study has been conducted on a nationwide basis. A survey conducted among a selected group of patients and nurses in Germany and the United Kingdom focused on the patients' preference for using Imraldi R pen versus Humira R or Enbrel R (etanercept) pens (5). Fenwick and colleagues demonstrated that most of their patients (78%) preferred to use the Imraldi R pen.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018 the Humira R patent expired in Europe, and its biosimilar Imraldi R was launched. Although Imraldi R has been shown to have comparable quality, efficacy and safety as Humira R (5,6), there is a difference among the two devices used to self-administration of the drugs. Both Humira R and Imraldi R are supplied with pre-filled pens containing 40 mg of the active substance adalimumab, but Humira R contains 0.4 mL of a sterile solution while Imraldi R contains 0.8 mL.…”
Section: Introductionmentioning
confidence: 99%
“…These results also confirmed those of other studies performed with biosimilar-autoinjectors that showed the preference of RA patients for injection mode with no push button and/or system with feedback after completion of injection. [12][13][14] Autoinjectors are designed to improve adherence, but self-injection is associated with a number of challenges including needle phobia, deformity and pain in the hands and fingers that can limit grip strength and severely impact the capacity of the patient to hold the device confidently and/or activate the injection correctly. 15 In clinical practice, although most patients prefer an autoinjector with no push button and appreciate to be informed of the end-ofinjection (as supported by the present survey and other studies), each patient would present with their own challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution may also be inappropriate if the patient will not be able to use the new product due to physical handicap or other relevant reasons. Nevertheless, the patients and healthcare providers may also consider a new device as easier to use 55–57. It is important that the physicians will have to present a clinically sound justification if they wish to prohibit the substitution.…”
Section: Discussionmentioning
confidence: 99%